A fast and accurate isotope dilution GC‐IT‐MS/MS method for determination of eugenol in different tissues of fish: Application to a depletion study in mandarin fish. (10th January 2018) - Liu, Yongtao; Ai, Xiaohui; Li, Le; Li, Jincheng; Yang, Hong
Abstract: An accurate, rapid and effective method was established for determination of eugenol in plasma, muscle, skin, liver, kidney and gill of fish using gas chromatography–ion trap tandem mass spectrometry. Samples of muscle, skin, liver, kidney and gill were prepared using the modified QuEChERS (quick, easy, cheap, effective, rugged and safe) procedure, and a plasma sample was prepared by a liquid–liquid extraction procedure. Eugenol was monitored in <7 min using an electron‐ionization source in MS/MS mode and quantified by an internal standard of eugenol‐d3 . The limit of detection was 5.0 μg/kg, and the limit of quantification was 10.0 μg/kg. The calibration curve was linear in the range of 5–1000 μg/L ( R 2 = 0.9996). Intra‐ and inter‐day precisions of eugenol expressed as relative standard deviation were within 9.74%, and the accuracy exhibited a relative error ranging from −2.20 to 8.89%. The developed method was successfully used to study the elimination regularity of eugenol in mandarin fish.